Routine Histopathological Examination of the Specimen After Laparoscopic Cholecystectomy: Can We Be Brave Enough to Give Up? - Kozan, Ramazan; Özaydın, Safa; Bayhan, Hüseyin; Leventoğlu, Sezai; Karamercan, Ahmet; Anadol, Ahmet Ziya; Şare, Mustafa; Aytaç, Abdülkadir Bülent (Turkish Journal of Gastroenterology, 2021)
investigate the effect of histopathology results on treatment modality and surgery strategy. The validity of the selective histopathology approach was questioned. Methods: The data of patients undergoing laparoscopic cholecystectomy between January 2009 and December 2019 were retrospectively analyzed. The demographics and histopathology results, whether the operation was emergent or elective, and the reasons for conversion to open surgery were recorded. Malignant and precursor histopathology diagnoses were examined, and their relationship with the surgical strategy was questioned. Results: A total of 2723 patients were included in the study. Of these patients, 2600 (95.5%) were operated under elective, while 123 (4.5%) were operated under emergency conditions. While the surgery was completed laparoscopically in 2685 (98.6%) patients, it was converted to open surgery in 38 (1.4%) patients. Age, gender, the presence of primary gallbladder cancer, acute cholecystitis, and xanthogranulomatous cholecystitis in histopathological examination were found to be independent predictive factors for conversion to open surgery (P < .05). The rate of primary invasive carcinoma in the series was 0.1%. Conclusion: Routine histopathological examination of the gallbladder is important for demonstrating a wide spectrum of pathological changes in this organ. Invasive cancer or precursor lesions can be detected even in patients without any macroscopic abnormality. Histopathological examination also plays a role in determining follow-up, further examination, and treatment modality in addition to the diagnosis in these patients.